From Fear to Adventure: How Trust, Risk, and Behavior Control Influence Gen Z's Solo Travel Intention - Meliana, Magsyanda; Yudhistira, Putu Gde Arie (Universitas Airlangga, 2025)
Objective: This study investigates the relationship between perceived risk and perceived behavioural control on Gen Z's solo travel intention mediated by trust. Design/Methods/Approach: A purposive sampling method was used to collect data through an online questionnaire using Microsoft Forms. A total of 404 respondents were collected from Gen Z. Data analysis was conducted using PLS-SEM through outer and inner models by using SmartPLS 4. Findings: The findings suggest that perceived risk and perceived behavioural control have a direct impact on solo travel intention. In addition, the mediating effect of trust has an indirect impact on solo travel intentions. Originality/Value: This study adds the mediating effect of trust in testing risk factors and behavioural control on Gen Z's solo traveling intention. The context of solo traveling remains under-researched in Gen Z, due to the relatively new phenomenon of solo traveling and the lack of Gen Z solo travellers. This research aims to fill the gap by highlighting these important aspects. Practical/Policy implication: This research provides several implications for practitioners, stakeholders and app developers in the tourism industry in making decisions to develop safe solo travel for potential solo travellers. Building cooperation to ensure safe destinations for solo travellers, creating solo travel apps, promoting safe solo travel on social media, and building flexible policies.